Pemanfaatkan Artificial Intelligence untuk Kegiatan Belajar Mengajar di Sekolah Dasar - Nugroho, Setiyo Adi; Prakasa Hadi, Andik; Rudjiono, Rudjiono; Zainudin, Ahmad; Priyadi, Agus (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The rapid advancement of computer technology, particularly artificial intelligence (AI), has a significant impact in educational sector. This influence spans all educational levels, from primary schools to universities. A Workshop was conducted to explore the use of AI as an educational aid, based on observations and interviews with theprincipal of Virgo Maria 2 Elementary School in Semarang Regency before the workshop. The goal was to familiarize the teachers with AI technology, highlighting both its advantages and disadvantages. The Workshop included both theoretical instruction and practical application of AI, guided by lecturers from the LPPM team from STEKOM University Semarang. Participants' understanding the usage of AI was assessed through their active engagement during the practical sessions of the Workshop . As a result, the participants are now have ability to utilize AI tools to enhance teaching and learning processes at VirgoMaria 2 Elementary School in Semarang Regency. The enhancement of teachers technical abilities in computer technology, especially in the use of artificial intelligence (AI), after the workshop, has achieved the destined goals..